2019
DOI: 10.1159/000496561
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Long- and Intra-Dialytic Blood Pressure Variability with All-Cause Mortality in Hemodialysis Patients

Abstract: Background: Blood pressure variability (BPV) is a potential prognostic predictor for all-cause mortality. Objectives: We conducted a retrospective cohort study to compare the prognostic value of long-term BPV with intra-dialytic BPV in hemodialysis (HD) patients. Materials and Methods: We included 611 HD patients and collected their baseline blood pressure (BP) measurements for 1 year and monitored them for 40 months. Long-term BPV was assessed by pre-dialysis BP SD and pre-dialysis absolute BP residual metric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Diastolic BPV has been reported to be associated with hemodialysis-related mortality [16], but this finding was not consistent in several other studies [10,[19][20][21]. Our analysis demonstrated that both systolic and diastolic BPV were significantly associated with all-cause mortality, whereas diastolic BPV failed to predict cardiovascular death.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Diastolic BPV has been reported to be associated with hemodialysis-related mortality [16], but this finding was not consistent in several other studies [10,[19][20][21]. Our analysis demonstrated that both systolic and diastolic BPV were significantly associated with all-cause mortality, whereas diastolic BPV failed to predict cardiovascular death.…”
Section: Discussioncontrasting
confidence: 86%
“…Thus, a total of 14 studies were included in this systematic review and meta-analysis (Fig. 1) [8][9][10][11][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…These alterations may subsequently affect the hemodynamic response of patients to ultrafiltration, thereby modifying their intradialytic BP profiles. The increased short-term BP variability with the consumption of intradialytic meals may also have prognostic implications if we take into consideration that observational studies have shown higher intradialytic BP variability to be associated with a higher risk for adverse cardiovascular events and mortality among patients on hemodialysis [ 18 , 19 ]. This risk association may be even stronger when increased BP variability is accompanied by a more frequent occurrence of symptomatic intradialytic hypotension, which is a serious and common dialysis-related complication that has also been associated with a heightened risk for cardiovascular morbidity and mortality [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The full texts of the remaining 49 articles were reviewed, and 34 were excluded because the population, exposure, or outcomes were not of interest or the article was a review, editor's comment, or reference abstract. One study presented overlapping data using the same datasets and was excluded [19]. Ultimately, the review included 15 eligible studies [18,[20][21][22][23][24][25][35][36][37][38][39][40][41][42].…”
Section: Data Synthesis and Statistical Analysismentioning
confidence: 99%
“…Studies have found an association between the mean BP and outcomes in patients on HD [15][16][17]. Over the last decade, more studies have explored the impact of BPV on the prognosis of HD patients, with inconsistent results [18][19][20][21][22][23][24][25]. Therefore, we conducted a systematic review and meta-analysis to assess the prognostic significance of BPV on cardiovascular and all-cause mortality and cardiovascular events in ESRD patients on dialysis.…”
Section: Introductionmentioning
confidence: 99%